Residual efficacy of pyrethrin + methoprene for control of Tribolium castaneum and Tribolium confusum in a commercial flour mill. (October 2015) - Arthur, Frank H.
Abstract: Concrete arenas with and without flour were placed in open, obstructed, and hidden positions inside a commercial flour mill and exposed to a combination treatment of pyrethrin + methoprene. Bioassays were conducted 1, 3, 5, and 7 weeks after the arenas were treated by adding flour to those arenas that were exposed without flour, and then placing late-stage larvae of either Tribolium castaneum (Herbst), the red flour beetle, or Tribolium confusum Jacqueline DuVal, the confused flour beetle, on an individual arena. There were no differences in adult emergence of either species on any of the exposed arenas in any position for the residual bioassays, indicating no loss of effectiveness of the insecticide. There was less adult emergence of both species on arenas that had contained flour when they were exposed to the aerosol compared to those exposed without flour and then flour added for the bioassay process. Adult emergence of both species was also lower in arenas with flour in the open position compared to those in the hidden and obstructed positions but regardless of exposure position or whether or not the arenas contained flour when they were exposed to the aerosol, adult emergence was greater in T. confusum than in T. castaneum . Results show how species variability and the presence of structural barriers within a facility can affect susceptibility to aerosol insecticides. Highlights: Tribolium confusum is more tolerant to pyrethrin + methoprene aerosol than Tribolium castaneum. Efficacy of aerosol systems in field sites may vary in efficacy. Insects in hidden or obstructed sites within flour mills may have limited exposure to aerosols.